A escolha da profissão docente: perfil dos alunos do curso de Pedagogia da UNESP/Bauru no ano de 2011 - Moraes, Fernanda Gomes de [UNESP] (Universidade Estadual Paulista (Unesp), 2012)
Several aspects interfere when it comes to choose a career. Some of which are family and cultural influence; and even lack of opportunities. Such aspects were greatly taken into consideration for defining the subject of this research which is to analyze the reasoning Pedagogy students from UNESP (Universidade Estadual Paulista – University of São Paulo State) used when choosing their academic career, and to assess the students’ profile who were taking this course in 2011 as well as the influence of students’ socioeconomic conditions. An empiric approach with a qualitative survey was chosen to develop this research which was conducted with a questionnaire appliance and with a semi-structured interview with randomly selected students. A theoretical study about the specifics of the academic career and a fully comprehension of the legal / regulatory aspects of this profession in Brazil were also conducted. The survey results showed that most students were women, supporting the fact that this career has become a female profession. Characteristics such as vocation and mission, presented on literatures as the specifics of this profession were clearly seen in the survey results. Several students went to public schools and are labeled into the classes C and D in social economical status; furthermore almost 50% had not chosen Pedagogy as a first choice for a major. However, most of the students do not think that their social economical status had influence in their choice. Nevertheless some students claimed that their options were not their first wish and their choice was made by the easier possibility of entering and concluding the course besides the prompt need of these professionals after graduating in the job market. The students’ education background were also discussed in the research... (Complete abstract click electronic access below)

Muitos aspectos interferem na escolha de uma profissão. Há desde a influência familiar e o fator cultural até a escolha decorrente da total falta de oportunidades. Tais aspectos tiveram grande impacto na definição do objeto desta pesquisa, que teve como objetivos analisar as razões da escolha da profissão docente por parte dos alunos do curso de Pedagogia da Faculdade de Ciências, UNESP/Bauru; verificar o perfil dos alunos que estavam realizando o curso no ano de 2011 e a influência das condições socioeconômicas dos alunos na escolha do curso. Para desenvolvê-la optamos por uma pesquisa empírica de base qualitativa que contou com a aplicação de um questionário e depois pela entrevista semi-estruturada com alguns alunos sorteados aleatoriamente. Optou-se também pelo aprofundamento teórico acerca da especificidade da docência e da compreensão dos aspectos legais/normativos que regulamentam a profissão de professor no Brasil. Os dados do questionário mostram que a maioria dos alunos é do sexo feminino, confirmando a feminização existente nessa profissão. Características como vocação e missão, apresentadas na literatura como uma das especificidades dessa profissão, não foram visivelmente verificadas nas respostas. Muitos dos alunos tiveram sua principal formação em escolas públicas e pertencem às classes C e D, e quase 50% não tiveram a Pedagogia como sua primeira escolha de curso. Entretanto, a maioria não acredita que a condição econômica e social influencia na escolha da profissão. Em contrapartida, nas entrevistas realizadas, alguns alunos afirmaram que a escolha pelo curso de Pedagogia não era a primeira opção no vestibular e que a escolha se fez pela facilidade em permanecer e finalizar o curso, além da possibilidade em obter um emprego ao término dos estudos... (Resumo completo, clicar acesso eletrônico abaixo)
Keywords: Educação - Estudo e ensino; Professores universitários; Educação - Brasil; Education - Study and teaching